2007
DOI: 10.14214/sf.311
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of geometric thinning systems and their time requirements for young forests

Abstract: In Fennoscandia, large areas that have not been subjected to pre-commercial thinning (PCT), and thus support dense stands, are becoming suitable for harvesting biomass. However, efficient systems for harvesting biomass from young stands have not yet been developed. In order to optimise biomass harvesting it is here hypothesized that the handling unit should not be a single tree but a corridor area, i.e., all trees in a specific area should be harvested in the same crane movement cycle. Three types of corridor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 14 publications
1
25
1
Order By: Relevance
“…Santesson & Sjunnesson, 1972;Wang et al, 2005), felling operations in environments similar to those considered in this study (e.g. Bergström et al, 2007;Iwarsson Wide & Belbo, 2009) and harvester and forwarder working patterns (e.g. Gullberg, 1997;Ovaskainen et al, 2004;Ovaskainen et al, 2006;Ovaskainen, 2008).…”
Section: Approach and Scenario Definitionsmentioning
confidence: 64%
See 2 more Smart Citations
“…Santesson & Sjunnesson, 1972;Wang et al, 2005), felling operations in environments similar to those considered in this study (e.g. Bergström et al, 2007;Iwarsson Wide & Belbo, 2009) and harvester and forwarder working patterns (e.g. Gullberg, 1997;Ovaskainen et al, 2004;Ovaskainen et al, 2006;Ovaskainen, 2008).…”
Section: Approach and Scenario Definitionsmentioning
confidence: 64%
“…Johansson & Gullberg, 2002). Towards this end, Bergström et al (2007) have compared the productivity potential of conventional and future (hypothetical) harvesting systems for forest fuel thinning (full trees) in young dense forests. They found that combining geometrical thinning systems (boomcorridor thinning) with customized techniques could increase productivity up to 2.4-fold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research and development specifically focusing on this are geometric thinning patterns [11,12], shown to have considerable potential, especially when used in combination with continuous cutting devices [13], multi-stem handling and pre-bunching in the stand for further processing [14][15][16]. Options for extraction including by forwarder [17,18], chipping in-field and extraction [19], and bundling of whole trees in-field [20,21] are methods with varying efficiencies in small trees.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there has been an increase in the amount of research and development aimed at identifying more efficient and cost-effective techniques and systems for energy wood extraction, involving new and improved approaches to extracting logging residues, stumps and whole trees from young stands (e.g. Bergström et al 2007). In other parts of the world forest haulage is most often done as skidding; partly carrying and partly dragging the logs, stems or trees.…”
Section: Literature Reviewmentioning
confidence: 99%